2019
DOI: 10.3390/ijgi8010024
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Standard Modeling Techniques Using Digital Aerial Imagery with National Elevation Datasets and Airborne LiDAR to Predict Size and Density Forest Metrics in the Sapphire Mountains MT, USA

Abstract: In recent years airborne Light Detection and Ranging (LiDAR) technology has received a great deal of attention. Using airborne LiDAR, analysts have successfully related height measurements to forest characteristics such as tree size, basal area, and number of trees. Similarly, National Agricultural Imagery Program (NAIP) digital aerial imagery in combination with elevation datasets such as the National Elevation Dataset (NED) have been used to estimate similar forest characteristics. Few comparisons, however, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…We were able to significantly improve estimates of the amount, location and condition of longleaf pine and other forest ecosystems across the Fort Stewart SGA using Landsat 8 imagery and FIA field data. Similar to other studies that relate field data with remotely sensed information to estimate aspects of the forested condition, BAH tended to be more strongly correlated with spectral metrics than TPH [12,[41][42][43]. Additionally, our study also supports the idea that multi-temporal imagery and finer resolution imagery such as NAIP provides additional information over using only single season imagery when predicting forest characteristics [41,44].…”
Section: Discussionsupporting
confidence: 87%
“…We were able to significantly improve estimates of the amount, location and condition of longleaf pine and other forest ecosystems across the Fort Stewart SGA using Landsat 8 imagery and FIA field data. Similar to other studies that relate field data with remotely sensed information to estimate aspects of the forested condition, BAH tended to be more strongly correlated with spectral metrics than TPH [12,[41][42][43]. Additionally, our study also supports the idea that multi-temporal imagery and finer resolution imagery such as NAIP provides additional information over using only single season imagery when predicting forest characteristics [41,44].…”
Section: Discussionsupporting
confidence: 87%
“…In this study, we showed that lidar-derived canopy metrics produced better models of forest structure when compared with Sentinel-2-only models, though this is not always that case, as [9] demonstrated. Additionally, when we combined imagery and lidar variables in our forest metric models, we created marginally better estimates for two out of our three forest metrics.…”
Section: Discussionmentioning
confidence: 57%
“…However, van Ewijk et al, 2011 used field data in combination with lidar data to estimate QMD, and not just to train their model [45]. Ahl et al, 2019 used random forest (RF) to model basal area and QMD from lidar, with RMSEs of 9.0 and 11.7, respectively [9]. These studies had higher lidar point densities and covered smaller study areas with a smaller range of forest types than our study, yet our best model results for BAH and QMD had similar or better r 2 and RMSE values (adj.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Single tree detection based on remote sensing images is a crucial technology for establishing a single tree database and monitoring single tree plantation resources, which is of great significance to urban landscape planning and ecological environment monitoring (Congalton et al, 2014;Faridatul and Wu, 2018;Ahl et al, 2019). Single tree detection is a cross-research field of computer vision, measurement, single tree management, and remote sensing (Kupidura et al, 2019;Zhang et al, 2020;Belcore et al, 2021).…”
Section: Introductionmentioning
confidence: 99%